Obszary metropolitalne Polski południowej a ruch migracyjny ludności; Metropolitan areas of southern Poland and population migration movement - Michal Bernard Pietrzak; Justyna Wilk (Institute of Economic Research (IER), 2013)
– The relations between metropolitan areas of southern Poland and domestic population migration flows in the period of 2008-2010 were discussed in this paper. Southern Polish regions demonstrate low intensity of intraregional population movements while interregional flows are quite significant, within considering territory. The majority of migration flows occur in relation to the cities of Wroclaw and Cracow, as regards neighbouring as well as remaining regions of Poland, due to their economic potential and metropolitan character.
Keywords: J11; O11; R11; R23; 330; internal migration; metropolitan area; synthetic measure of development